Structural Approach in International Relations and Its Limits: Domestic Variables as an Alternative Approach - Dhungel, Rudra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2023)
For a long time, the study of Nepal's foreign policies has been concentrated on a power-centric structural approach, essentially realism, which remains the dominant approach to analyzing foreign policy of Nepal. The objective of this paper is to point out the gaps that realism fails to explain when it comes to the matter of the foreign policy analysis of Nepal and provides an alternative approach of also looking into the domestic determinant like national policies, party system, historical context and social structure of Nepal and other domestic determinants that are influencing Nepal's foreign policy's behaviour besides Nepal's geo-political location. The research used extensive discourse analysis as a methodology to show that limiting to structural realism to analyze Nepal's Foreign policy behaviour has produced narrow-understanding of the subject, and it is essential to go beyond the structural approach and have a more critical approach to have much nuance understanding of Nepal foreign policy and what impacts it.